Adult-Onset Still's Disease Masquerading as Hemophagocytic Lymphohistiocytosis - Pooja Gautam; Navneet Gupta; Aanchal Arora; Kusha Sharma; Atul Goel (Indian Journal of Medical Specialities)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hematological condition caused by the overactivation of macrophages leading to widespread tissue destruction and organ dysfunction. The disease has a clinical overlap with adult-onset still's disease (AOSD) and hence poses a diagnostic challenge. We report the case of a 20-year-old female who presented with prolonged febrile illness, anemia, hepatosplenomegaly, and generalized lymphadenopathy. She was diagnosed with HLH and was readmitted 6 weeks later with recurrent fever, polyarthralgia, and pharyngitis. A diagnosis of AOSD with secondary HLH was made.